2022
DOI: 10.3390/nu14122551
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Dietary Patterns and Pre-Pregnancy BMI with Gestational Weight Gain: The “Born in Shenyang” Cohort

Abstract: The reported associations of maternal dietary patterns during pregnancy with gestational weight gain are inconsistent, especially among the less studied Asian Chinese populations. In a prospective pre-birth cohort study conducted in northern China, we determined the associations between maternal dietary patterns and the probability of excess gestational weight gain (EGWG) among 1026 pregnant women. We used 3-day food diaries to assess maternal diet and performed principal component analysis to identify dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 33 publications
(70 reference statements)
0
14
0
Order By: Relevance
“…In the present study, we observed evidence that the association between maternal dietary patterns and the development of GH is stratified by maternal pre-pregnancy weight status. Previous studies have indicated that the association between maternal prenatal dietary patterns and the risk of GDM [ 17 ] or gestational weight gain [ 18 ] is stratified by women’s BMI levels. To our knowledge, ours is the first study to report the effect of the interaction between maternal dietary patterns and pre-pregnancy weight status on maternal GH risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we observed evidence that the association between maternal dietary patterns and the development of GH is stratified by maternal pre-pregnancy weight status. Previous studies have indicated that the association between maternal prenatal dietary patterns and the risk of GDM [ 17 ] or gestational weight gain [ 18 ] is stratified by women’s BMI levels. To our knowledge, ours is the first study to report the effect of the interaction between maternal dietary patterns and pre-pregnancy weight status on maternal GH risk.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the linear trend between dietary patterns and pregnant women’s blood pressure, we took the median score of each dietary pattern quartile as a continuous variable, and reported the p -for-trend in multivariable models. Previous studies have reported that associations between maternal diet and complications of pregnancy may be modified by women’s pre-pregnancy weight status [ 17 , 18 ]. Therefore, we further examined the potential effect modification of maternal pre-pregnancy BMI (overweight/obese [OwOb] [BMI < 24 kg/m 2 ] vs. non-OwOb [BMI ≥ 24 kg/m 2 ]) by including multiplicative interaction terms in the models.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, we classified the dietary patterns in the included articles into three categories: healthy dietary patterns, [16][17][18][19]21,22,[24][25][26][27] unhealthy dietary patterns, [18][19][20][21][22]26,28,29 and mixed dietary patterns. [18][19][20][21][22][27][28][29][30] Healthy dietary patterns are characterized by high intake of fruits, vegetables, soy products, whole grains, fish, seafood, low-fat yogurt, olive oil, low-fat dairy, nuts, and legumes.…”
Section: Definition Of Dietary Patternsmentioning
confidence: 99%
“…[18][19][20] This is in contrast to the results of a cohort study from Shenyang, China, where a negative association between sweet food patterns and EGWG was established. 21 Another study 22 failed to establish a significant association between a dietary pattern characterized by the higher intake of cake, coffee, sugary fizzy drinks, alcohol, sweets, and fast food and EGWG. A previous review paper 23 showed that neither healthy nor unhealthy dietary patterns are significantly associated with EGWG.…”
Section: Introductionmentioning
confidence: 99%